2015
DOI: 10.1093/ehjci/jev110
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography and intravascular ultrasound evaluation of cardiac allograft vasculopathy with and without intimal neovascularization

Abstract: OCT-identified microchannels increased sharply within the first year and were correlated with intimal volume and coronary risks. This suggests that neovascularization may play an important role in the progression of cardiac allograft vasculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
3
12
0
1
Order By: Relevance
“…In this analysis, we link intimal neovascularization observed by OCT to co-incident CAV, establishing an association between IN visualization and clinical outcomes. Importantly, we also provide further demonstration of IN associations noted in small series by other investigators [5][6][7].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this analysis, we link intimal neovascularization observed by OCT to co-incident CAV, establishing an association between IN visualization and clinical outcomes. Importantly, we also provide further demonstration of IN associations noted in small series by other investigators [5][6][7].…”
Section: Discussionsupporting
confidence: 81%
“…Ichibori et al reported increased intimal neovascularization at greater than 1-year posttransplant, which corroborates our finding of a significant association of INs with increasing transplant age. We also similarly observed an association between increasing MIT and the presence of INs (p < 0.001) [6]. We did not observe a significant association between INs and recipient hyperlipidemia, diabetes or prior CMV infection, as described by other authors, but did note an association with recipient hypertension [6,8].…”
Section: Corroboration With Prior Seriessupporting
confidence: 87%
“…Multilayer appearance was associated with increase in plaque volume, necrotic core volume, and dense calcium volume and was found to be a potential predictor of plaque progression. OCT imaging also revealed that coronary microchannels, which indicate intimal neovascularization, are a novel and relevant morphological marker of CAV progression . OCT imaging also confirmed typical features of CAV .…”
Section: Discussionmentioning
confidence: 73%
“…Odhalení skutečné hlavní příčiny CAV si vyžádá prospektivní studie zaměřené na protilátky proti dárcovsky specifi ckému lidskému leukocytárnímu antigenu v oběhu [32,33], které budou současně používat nové zobrazovací metody, jako např. optickou koherenční tomografi i [34].…”
Section: Diskuseunclassified